(untitled) (Global Journal of Medical Research, 2023)
Introduction The elderly undergo biopsychosocial and functional changes that reduce their ability to adapt to the environment In addition pathological processes occur that make the elderly more susceptible to frailty Methodology The methodology used for this analysis was based on a literature review in which the sources were obtained from the SciELO Google Scholar and PubMed data platforms Discussion Ageing raises concerns about the impact on the quality of life of these individuals Lenardt et al 2016 According to Who 1995 quality of life is an individual s perception of their position in life according to the context in which they live and their relationship with expectations goals and concerns In this sense it can be seen that quality of life suffers from internal and external influences Jesus et al 2018